Evaluation of Ethnopharmacological and Antioxidant Potential of Zanthoxylum armatum DC. - Rabia Kanwal; Muhammad Arshad; Yamin Bibi; Saira Asif; Sunbal Khalil Chaudhari (Journal of Chemistry)
Zanthoxylum armatum DC. (syn. Z. alatum Roxb.) is an important medicinal plant commonly called Timur or Indian prickly ash. The ethnopharmacological study of Z. armatum revealed the use of different plant parts for curing various ailments including cholera, chest infection, fever, indigestion, stomach disorders, gas problems, piles, toothache, gum problems, dyspepsia, as carminative, antipyretic, aromatic, tonic, and stomachic. Keeping in view the medicinal potential of the plant, the antioxidant activity was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging, reducing power, and phosphomolybdate assay using different concentrations (7.81 μg/mL–250 μg/mL). Ascorbic acid was taken as standard. The results indicated that the free radical scavenging activity ranged from 40.12% to 78.39%, and the reductive potential ranged from 0.265 nm to 1.411 nm while the total antioxidant activity ranged from 0.124 nm to 0.183 nm. The antioxidant potential evaluated by three assays increased in a concentration dependent manner and ascorbic acid showed better antioxidant activity than leaf extract. Results obtained through different tests confirmed redox protective activities of Zanthoxylum armatum. Further in vitro and in vivo research should be performed, so this plant can be further utilized in drug development.